2019
DOI: 10.1039/c9ob01535c
|View full text |Cite
|
Sign up to set email alerts
|

Dual-quenching NBD-based fluorescent probes for separate detection of H2S and Cys/Hcy in living cells

Abstract: Dual-quenching fluorescent probes based on thiolysis of NBD thioether/ether/amine for fast and separate detection of H2S and Cys/Hcy in living cells were rationally constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…In the previous studies, we noticed that H 2 S and Cys can readily recognize by nucleophilic aromatic substitution (S N Ar) with electrophilic NBD derivatives to generate NBD-SH and NBD-SR compounds, upon treatment with Cys, NBD-Cys showed fluorescence, while reaction with H 2 S produced non-fluorescent NBD-SH. 35–40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies, we noticed that H 2 S and Cys can readily recognize by nucleophilic aromatic substitution (S N Ar) with electrophilic NBD derivatives to generate NBD-SH and NBD-SR compounds, upon treatment with Cys, NBD-Cys showed fluorescence, while reaction with H 2 S produced non-fluorescent NBD-SH. 35–40…”
Section: Resultsmentioning
confidence: 99%
“…In the previous studies, we noticed that H 2 S and Cys can readily recognize by nucleophilic aromatic substitution (S N Ar) with electrophilic NBD derivatives to generate NBD-SH and NBD-SR compounds, upon treatment with Cys, NBD-Cys showed fluorescence, while reaction with H 2 S produced nonfluorescent NBD-SH. [35][36][37][38][39][40] Inspired by the above design ideas, 41 a dual-fluorophore and dual-site fluorescent probe (Cy-NP) was constructed for the assessment of H 2 S and Cys separately and continuously. Firstly, Cy-NP possessed two fluorophores with comparable maximum emission wavelength distances, a fluorophore that emitted in the NIR channel of 700-800 nm and the other that emitted in the visible region of 500-600 nm, meaning that the emission bands of the two fluorophores could reduce mutual interference during detection.…”
Section: Design Of Cy-npmentioning
confidence: 99%
“…As shown in Figures F and S4, the addition of Cys and Hcy can cause significant fluorescence changes, while the changes caused by other analytes can be ignored. Since the amount of Hcy in normal organisms (below 12–15 μM) is much lower than that of Cys (30–200 μM), , the interference of Hcy can also be ignored. Considering the low fluorescence intensity observed after 40 min of Hcy addition, it can be concluded that the potential interference of Hcy is negligible (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…35,36 Certain probes utilizing nucleophilic reaction and CuS precipitation strategies are vulnerable to other reactive sulfur species (RSS). 37,38 Taking the above factors into consideration, it is also of great significance to search for a H 2 S-responsive probe with high selectivity.…”
Section: Introductionmentioning
confidence: 99%